2012
DOI: 10.1017/s0022377812000980
|View full text |Cite
|
Sign up to set email alerts
|

Phase shifts of magneto-acoustic solitons in spin-1/2 fermionic quantum plasma during head-on collision

Abstract: The head-on collision between two magneto-acoustic solitons in spin-1/2 fermionic quantum plasma is studied in the framework of the model proposed by Marklund et al. (Marklund, M., Eliasson, B. and Shukla, P. K. 2007 Phys. Rev. E. 76, 067401). The extended Poincare–Lighthill–Kuo method is used to obtain the phase shifts and the trajectories during the head-on collision of two solitons. The effect of the Zeeman energy for different speeds of the waves, the effect of the total mass density of the charged plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The head-on collision of ion-acoustic solitary waves in plasma with nonextensive distributed electrons is examined in [38], they found that the nonextensive distribution electrons important role in the properties of ion-acoustic solitary waves collision. A recent study has investigated the collision of ions acoustic solitary waves in various plasma environments see in [39][40][41][42]. The ion collisions in plasma have already been established experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The head-on collision of ion-acoustic solitary waves in plasma with nonextensive distributed electrons is examined in [38], they found that the nonextensive distribution electrons important role in the properties of ion-acoustic solitary waves collision. A recent study has investigated the collision of ions acoustic solitary waves in various plasma environments see in [39][40][41][42]. The ion collisions in plasma have already been established experimentally.…”
Section: Introductionmentioning
confidence: 99%